Catatan Kang Jalal : visi media, politik, dan pendidikan - Rakhmat, Jalaluddin, 1949-; Rakhmat, Miftah F. (Bandung : Remaja Rosdakarya, 1997)
Mass media, political conditions, and education in Indonesia; collection of articles.
Errata slip inserted at end.
Includes indexes.
Keywords: Mass media -- Indonesia; Mass media -- Political aspects -- Indonesia; Education -- Indonesia